The attitudes of medical students to research - Nel, D; Burman, R; Hoffman, R; Randera-Rees, S (Health and Medical Publishing Group, 2013)
BACKGROUND: The workforce of 'physician-scientists' is ageing and decreasing in numbers. The responsibility to combat this trend rests on future generations of healthcare professionals and it is therefore valuable to evaluate medical students' attitudes towards research. OBJECTIVE: To establish the attitudes of University of Cape Town (UCT) medical students towards research and to investigate the factors influencing these attitudes. METHODS: An anonymous, cross-sectional, self-administered questionnaire was administered to medical students from years 1 to 6 studying medicine at UCT in 2011. Questions were primarily closed-ended and consisted of Likert scales. RESULTS: Out of a population of 1 195 medical students, 733 were sampled (63%); 65% were female, 53% were preclinical students (years 1 - 3) and 47% were in their clinical years (year 4 - 6). Overall, 61% of students had a positive attitude towards research and 74% felt that participation in research was important to their medical school education; 22% had been involved in voluntarily extracurricular research, 4% had presented at a scientific meeting and 3% had published in peer-reviewed journals. A number of perceived barriers to student research were identified including a lack of adequate training, time and research opportunities. CONCLUSION: Students believed that research was important and had a positive attitude towards it. However, few had been involved in voluntary research and produced work worthy of presentation and/or publication. Addressing identified barriers and improving students' attitudes may begin to reverse the trend in declining numbers of physician-scientists.